2015
DOI: 10.1111/bpa.12331
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of Hypoperfusion of the Precuneus in Early Alzheimer's Disease

Abstract: The earliest decline in cerebral perfusion in Alzheimer's disease (AD) is in the medial parietal cortex (precuneus). We have analyzed precuneus in post‐mortem tissue from 70 AD and 37 control brains to explore the pathophysiology of the hypoperfusion: the contribution of arteriolosclerotic small vessel disease (SVD) and cerebral amyloid angiopathy (CAA), and of the vasoconstrictors endothelin‐1 (EDN1) and angiotensin II (Ang II), and the association with Aβ. The myelin‐associated glycoprotein:proteolipid prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 57 publications
5
88
0
Order By: Relevance
“…Our own studies found the MAG:PLP1 ratio to be reduced in the cerebral cortex in late, as well as early AD (75,134). However, within the precuneus, the ratio was not as markedly decreased in brain tissue from patients with Braak stage V-VI disease as in those with earlier (Braak stage III-IV) disease and not significantly so in comparison with Braak stage 0-II disease (Figure 2).…”
Section: Reduced Demand or Reduced Supply?mentioning
confidence: 80%
See 2 more Smart Citations
“…Our own studies found the MAG:PLP1 ratio to be reduced in the cerebral cortex in late, as well as early AD (75,134). However, within the precuneus, the ratio was not as markedly decreased in brain tissue from patients with Braak stage V-VI disease as in those with earlier (Braak stage III-IV) disease and not significantly so in comparison with Braak stage 0-II disease (Figure 2).…”
Section: Reduced Demand or Reduced Supply?mentioning
confidence: 80%
“…We showed that the MAG:PLP1 ratio, was reduced in the precuneus by ~50% in Braak stage III-IV disease (75), indicating that even in early AD there is a disparity between oligodendrocyte energy demand and supply in the first region of brain to show hypoperfusion.…”
Section: Reduced Demand or Reduced Supply?mentioning
confidence: 86%
See 1 more Smart Citation
“…Blood flow and oxygenation are reduced in the cerebral cortex and underlying white matter in Alzheimer's disease (AD) [1][2][3][4][5][6][7]. Cerebral blood flow (CBF) declines before cognitive decline or brain atrophy [1,8] and is associated with biochemical and MRI evidence of tissue damage [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Cerebral blood flow (CBF) declines before cognitive decline or brain atrophy [1,8] and is associated with biochemical and MRI evidence of tissue damage [4,9]. Vessel wall abnormalities such as cerebral amyloid angiopathy (CAA) and arteriolosclerosis, may play a part in the hypoperfusion but its timing and distribution suggest that other factors are more important contributors.…”
Section: Introductionmentioning
confidence: 99%